POLICY OF TAX LAW ENFORCEMENT PANDEMIC AND POST PANDEMIC COVID 19 IN INDONESIA - Bambang Ali Kusumo (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2022)
Law enforcement in the field of taxation requires administrative and criminal sanctions. In certain circumstances, namely forced circumstances (overmacht or force majeure), the legal sanctions may not be enforced or their implementation postponed due to disasters that hit the community, including in this case the Covid 19 pandemic. The existence of this covid 19 pandemic will affect law enforcement in the field of taxation. Many taxpayers have difficulty in developing their business. The impact of this causes taxpayers to find it difficult to pay off their obligations to pay taxes. In view of this, the Government must issue a policy that is not burdensome to taxpayers. The purpose of this paper is to analyze Law Enforcement Policies in the Taxation Sector during the pandemic and post-Covid 19 pandemic in Indonesia. The main data source used in this writing is secondary data, namely Law no. 28 of 2007 concerning General Provisions and Tax Procedures (KUP), Government policies related to taxation that do not burden taxpayers, both Central and Regional Government policies. The results show that Government Policy in tax law enforcement during the Pandemic and post-Covid-19 pandemic provides tax incentives and tax relaxation to the public, especially the business world, so that its existence is still ongoing. After the Covid 19 pandemic, the Government took a policy of optimizing tax revenues, focusing on VAT, tax regulations, optimizing tax revenues through the expansion of the tax base. Keywords: Law Enforcement, Taxes, Covid and post Covid 19